THE ABILITY IN USING IDIOMATIC EXPRESSION BY STUDENTS OF NUSA CENDANA UNIVERSITY - Seran, Yanuarius (Jurnal Pendidikan Bahasa Inggris undiksha, 2020)
This study aimed to investigate how far the sixth-semester students specifically class A of English Study Program of Nusa Cendana University comprehended idiomatic expressions, and what appeared to be the issues in comprehending it. A descriptive method was utilised to analyse the data. In collecting the data, a set of tests and questionnaires were employed. The result showed that the students’ comprehension of idiomatic expression was 43.21% which was classified as at a fair level. There were some factors contributing to this condition. (1) The students tended to interpret the idiomatic expression literally. (2) lack of knowledge about the culture’s background of the target language. This is because idiomatic expression couldn’t be interpreted literally. Then, the problems were faced by the students were lack of vocabulary, and idiomatic expressions which were still new for the students.